Addressing Power and Solidarity in TV Subtitling - Pavlović, Nataša (Array, 2004)
Subtitling for television is an area that has only recently found its niche in Translation Studies. This paper, based on the author's M.A. research into a corpus of subtitled material shown on Croatian television (HRT), is a modest contribution to the growing sub-field(s) of Translation Studies variously referred to as 'screen translation', 'audiovisual translation' (AVT) or, more broadly, 'multimedia translation'. The paper offers a brief survey of key features of subtitling and then goes on to illustrate how these may shed light on particular aspects of translation in general. The analysis focuses on interpersonal relations between the fictional characters of a popular U.S. TV series (ER) and examines what happens to those relations when the audiovisual source product is subtitled for the audience of a nationwide, public TV network in south-eastern Europe. The constraints inherent to the subtitling technique prove useful for isolating particular pragmatic elements and examining their function in the achievement of the overall communicative goal. The analysis focuses on various forms of address, which are examined in terms of the pragmatic notions of 'power' and 'solidarity'. The approach is a descriptive one, applying the theoretical framework and analytical tools adopted from Hatim and Mason (1990 and 1997) and Mason (1989).